2005
DOI: 10.1039/b416852f
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature CO oxidation over iron-containing MCM-41 catalysts

Abstract: Different MCM-41 samples containing framework iron were prepared and tested in CO oxidation showing unprecedented high activities after reduction in hydrogen above 773 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…The synthesis of mesoporous (2-50 nm) silicas M41S in 1992 using a supramolecular surfactant system as a template provoked a great ''Boom'' in the field of nanoporous materials [1][2][3][4][5][6][7]. In particular, a special attention has been devoted to develop mesostructured aluminosilicates since aluminosilicate is one of important chemical compositions in catalysis and separation processes of high molecular weight petroleum fractions [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of mesoporous (2-50 nm) silicas M41S in 1992 using a supramolecular surfactant system as a template provoked a great ''Boom'' in the field of nanoporous materials [1][2][3][4][5][6][7]. In particular, a special attention has been devoted to develop mesostructured aluminosilicates since aluminosilicate is one of important chemical compositions in catalysis and separation processes of high molecular weight petroleum fractions [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The net result of this interaction is a perturbation of the CO molecule leading to its high reactivity even at low temperatures. This concept has been recently extended to the Fe-MCM41 type catalyst, which showed high activity in low temperature CO oxidation after its reduction in hydrogen above 500 o C [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, the preparation of stable, modified materials by conventional hydrothermal synthesis is usually possible at low metal loading, which strongly restricts the application as catalysts. It has been recently reported that the sol-gel technique reveals much higher ability in this aspect, and the preparation of stable metal modified MCM-41 materials were obtained [12,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established, that the applied method of modification strongly influences the state (localization, dispersion and oxidative state) of the loaded metal species [12][13][14][15]. Their introduction in the host matrix could be realized during the silica synthesis procedure as well as by various postsynthesis techniques (impregnation, grafting) [12][13][14][15][16]. However, the preparation of stable, modified materials by conventional hydrothermal synthesis is usually possible at low metal loading, which strongly restricts the application as catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation